Quality of life and GERD incidence in medical students: A cross-sectional study - Saragih, Agnes Fransisca; Purba, Desi Natalia; Silaen, Mangatas; Fibrini, Dewi (Jurnal Prima Medika Sains, 2023)
Medical students are highly susceptible to GERD due to the intense pressure and hectic pace of medical education. Risk factors for GERD in medical students include inadequate knowledge, poor dietary habits, frequent coffee consumption, and high stress levels. This cross-sectional study enrolled 250 students. Data were analysed using chi-squared test and logistic regression. The results showed a significant association between knowledge (0.000), diet (0.000) and coffee consumption (0.002) with GERD in medical students. Stress was not a significant risk factor in this study (0.127). Regression modelling showed that improving diet can minimise the risk of GERD by a factor of one. There is a need to improve diet and lifestyle in medical students to minimise GERD.